A polyvalent coral snake antivenom with broad neutralization capacity - Castillo-Beltrán, María Carlina (PLoS Negl Trop Dis, 2019)
Coral snakes of the genus Micrurus have a high diversity and wide distribution in the Americas. Despite envenomings by these animals being uncommon, accidents are often severe and may result in death. Producing an antivenom to treat these envenomings has been challenging since coral snakes are difficult to catch, produce small amounts of venom, and the antivenoms produced have shown limited cross neutralization. Here we present data of cross neutralization among monovalent antivenoms raised against M. dumerilii, M. isozonus, M. mipartitus and M. surinamensis and the development of a new polyvalent coral snake antivenom, resulting from the mix of monovalent antivenoms. Our results, show that this coral snake antivenom has high neutralizing potency and wide taxonomic coverage, constituting a possible alternative for a long sought Pan-American coral snake antivenom.